(3eYGfi GdbQBfs - (3CMeO Hf eMeO Hf ESeGYjd GdeUQj GdfMhj, CHh LYaQ , GHf GdfMGS, J (B338 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ ShQI GdaGJMI s
(3BNQgG (B:s
(3jfJgi HJaSjQ ShQI eQje s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B208s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1730s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdJaSjQ hYdhe GdbQBfs